Bases of subalgebras of K〚x〛 and K[x]. (March 2017) - Assi, A.; García-Sánchez, P.A.; Micale, V.
Abstract: Let f 1, …, f s be formal power series (respectively polynomials) in the variable x . We study the semigroup of orders of the formal series in the algebra K 〚 f 1, …, f s 〛 ⊆ K 〚 x 〛 (respectively the semigroup of degrees of polynomials in K [ f 1, …, f s ] ⊆ K [ x ] ). We give procedures to compute these semigroups and several applications. We prove in particular that the space curve parametrized by f 1, …, f s has a flat deformation into a monomial curve.